Institute of Small Enterprises and Development - Planning Commission (Planning Commission, 1990)
Small enterprises is now very much part of the common jargon of both the learned and the laymen. However neither this nor related terms such as informal sector unorganised sector etc. can claim any unambiguous connotation or a clear unique shape to form part of a theoretical model. Planning, on the other hand deals with exact well-defined concepts entities and categories which can be clearly delimited and directly controlled by specific policy measures.
Government of India Planning Commission
Government of India Planning Commission